2016
DOI: 10.1002/ca.22686
|View full text |Cite
|
Sign up to set email alerts
|

Prader–Willi Syndrome: A spectrum of anatomical and clinical features

Abstract: Prader-Willi Syndrome (PWS) is estimated to affect 400,000 people worldwide. First described clinically in 1956, PWS is now known to be a result of a genetic mutation, involving Chromosome 15. The phenotypical appearance of individuals with the syndrome follows a similar developmental course. During infancy, universal hypotonia accompanied by feeding problems, hypogonadism, and dolichocephaly are evident. Characteristic facial features such as narrow bifrontal diameter, almond-shaped eyes, and small mouth (wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 151 publications
(407 reference statements)
0
28
0
Order By: Relevance
“…Our earlier study has demonstrated an increased risk for NDDs in Klinefelter syndrome, which has hypogonadism as one of the clinical features . NDDs and hypogonadism also co‐occur in other defined genetic syndromes such as Turner, Prader‐Willi, Bardet‐Biedl and CHARGE syndromes . Additionally, hypospadias, a common congenital malformation, which is sometimes caused by androgen insufficiency, increase the risk of an NDD …”
Section: Introductionmentioning
confidence: 99%
“…Our earlier study has demonstrated an increased risk for NDDs in Klinefelter syndrome, which has hypogonadism as one of the clinical features . NDDs and hypogonadism also co‐occur in other defined genetic syndromes such as Turner, Prader‐Willi, Bardet‐Biedl and CHARGE syndromes . Additionally, hypospadias, a common congenital malformation, which is sometimes caused by androgen insufficiency, increase the risk of an NDD …”
Section: Introductionmentioning
confidence: 99%
“…The worldwide incidence of severe classic CAH is 1 in 15,000 [10] and the incidence of PWS is estimated to be between 1 in 10,000 and 1 in 30,000 [11]. …”
Section: Discussionmentioning
confidence: 99%
“…In individuals with individuals commonly have obesity3 and may present hypogonadism4 and growth hormone deficiency (GHD) 5 6. Consequently, they appear to be at high risk of vascular disease due to obesity-related cardiovascular risk factors, such as hypertension, diabetes mellitus type 2 or obstructive sleep apnoea syndrome 4 6 7…”
Section: Introductionmentioning
confidence: 99%